1975
DOI: 10.1111/j.1471-4159.1975.tb07696.x
|View full text |Cite
|
Sign up to set email alerts
|

THE ELEVATION OF CEREBRAL HISTAMINE‐N‐AND CATECHOL‐O‐METHYL TRANSFERASE ACTIVITIES BY l‐METHIONINE‐dl‐ SULFOXIMINE1

Abstract: Abstract— The administration of the convulsant, l‐methionine‐dl‐sulfoximine (MSO), increased histamine N‐methyl transferase (E.C. 2.1.1.8) (HMT) activity in rat and mouse brain and, to a lesser extent, catechol‐O‐methyl transferase (E.C. 2.1.1.6) (COMT) activity in rat brain. The duration of this effect was shortened by co‐administration of l‐methionine. The increased HMT activity was seen in 5 or 7 rat brain regions tested. l‐Methionine administration had no effect on the activity of either enzyme. Partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1976
1976
1984
1984

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…We have also investigated the validity of using the AdoMet/AdoHcy ratio as an index of transmethylation activity of brain tissue, as has been previously suggested (2,7).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also investigated the validity of using the AdoMet/AdoHcy ratio as an index of transmethylation activity of brain tissue, as has been previously suggested (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to elucidate the mechanism(s) responsible for the seizureproducing properties of methionine sulfoximine (MSO) have demonstrated that this agent alters methylation processes in brain. Administration of MSO resulted in (a) decreased levels of cerebral S-adenosylmethionine (AdoMet) in the rat (1), (b) increased activity of histamine-Nmethyltransferase (HMT) in rat and mouse brain (2), and (c) increased activity of catechol-O-methyltransferase (COMT) in rat brain (2,3). The lack of effect of MSO (in vivo or in vitro) on the activity of the enzyme responsible for AdoMet synthesis (ATP:L-methionine-S-adenosyltransferase) (4,5), paired with the finding of the elevated cerebral HMT and COMT activity (in vivo) (2), has led to the suggestion that MSO acts by increasing the flux through methylation pathways (2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the discovery of MSO, there have been several studies to identify its mechanism(s) of action in animals. It has been shown to cause anatomical changes (4,5,9,16,19) in the brain structure of laboratory animals and in order to further clarify the effect of MSO on the brain its action on several brain neurochemical parameters has been studied, including glycogen and related enzymes (2,6,7,16), amino acid metabolism (8,15,26,27), ammonia (7), brain amines and their enzymes (5,21,25) as well as other enzyme systems in mammalian brain (5,10,11,20,23,24). It has also been demonstrated that the amino acid, methionine, can antagonize the uptake and binding of MSO in certain brain areas (22) as well as some of its effects (12,18).…”
Section: Introductionmentioning
confidence: 99%